Assessing breast self-examination knowledge, attitude and practice as a secondary prevention of breast cancer among female undergraduates at the University of Dodoma: a protocol of analytical cross-sectional study - Masawa, Glory; Mboineki, Joanes Faustine (Frontiers in Epidemiology, 2024)
Background Breast cancer is a global disease affecting an enormous number of women worldwide and a primary cause of cancer-related deaths in women. In Tanzania, women's breast cancer is the second-ranked among all types of cancers, with an incidence of 15.9%. Despite the Breast Self Examination (BSE) being one of the secondary prevention of breast cancer and an important measure for early diagnosis of breast cancer, little is known whether women could practice routine BSE. Objectives The study aims to Assess breast self-examination (BSE) knowledge, attitude, and practice among female undergraduates at the University of Dodoma. Methodology An institutionally-based analytical cross-sectional study will be carried out in the Dodoma region of Tanzania through a validated questionnaire. The study will involve 384 female undergraduate students aged 18 years. The data will be entered and analyzed in the Statistical Package for Social Sciences (SPSS) Version 25. Descriptive analysis (frequencies and percentages) and inferential statistics [Cross-tabulation, Chi-square (χ2), and Regression analysis] will be used. Conclusion The practice of BSE among women remains unsatisfactory, which is highly linked to the lack of BSE knowledge. The deficit knowledge is on how to perform BSE, the benefit of BSE, and the interval of doing BSE. Most of the women seem to possess a positive attitude towards BSE.